Molecular and Phenotypic Analyses of Inpari HDB/K15 F2 Lines Containing sd1 Mutant Gene Resulted from Genome Editing Method - Clara S. A. Fitriyanti; Suharsono Suharsono Suharsono; Tri Joko Santoso (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2020)
Inpari HDB variety is resistant to bacterial leaf blight (BLB) disease, but due to its tall stature, the variety is susceptible to lodging. Inpari HDB with semidwarf stature, therefore, is of high interest for lodging resistant performance. sd1 gene encoding GA20ox-2 enzyme is one of the genes responsible for imparting semidwarf stature of rice. In previous study, sd1 mutant rice cv. Kitaake (K15) was developed by using CRISPR/Cas9 technology. The objective of this study was to analyze molecularly and phenotypically F2 lines containing sd1 mutant gene resulted from a cross between Inpari HDB and K15 to develop semidwarfInpari HDB rice variety. Thirty F2 Inpari HDB/K15 lines were analyzed at molecular level using DNA sequencing method together with phenotypic assessment of the lines to verify the integration of sd1 mutant gene. DNA sequencing analysis showed that 9 out of the 30 F2 Inpari HDB/K15 lines were sd1 mutants. The remaining F2 lines contained 17 heterozygotes and 4 nonmutants. All the nine mutant lines demonstrated shorter plant stature and showed more tiller number per plant compared to the nonmutant lines. The sd1 mutant gene in the F2 lines showed pleiotropic effects on panicle number andshowed no effects on other traits, such as flowering time, panicle length, filled and unfilled grain percentages. This study showed the introduction of sd1 mutant gene generated semidwarf Inpari HDB lines. The semidwarf Inpari HDB lines obtained from this research should be further evaluated to confirm their lodging resistant performances.